Binocular rivalry alternations and their relation to visual adaptation - Roumani, Daphne; Moutoussis, Konstantinos (Frontiers in Human Neuroscience, 2012)
When different stimuli are presented dichoptically, perception alternates between the two in a stochastic manner. After a long-lasting and rigorous debate, there is growing consensus that this phenomenon, known as binocular rivalry, is the result of a dynamic competition occurring at multiple levels of the visual hierarchy. The role of low- and high-level adaptation mechanisms in controlling these perceptual alternations has been a key issue in the rivalry literature. Both types of adaptation are dispersed throughout the visual system and have an equally influential, or even causal, role in determining perception. Such an explanation of binocular rivalry is also in accordance with the relationship between the latter and attention. However, an overall explanation of this intriguing perceptual phenomenon needs to also include noise as an equally fundamental process involved in the stochastic resonance of perceptual bistability.